Il Polittico : Stagione espositiva 2004-2005. (Roma : Il Polittico - Associazione d'Arte e Cultura Roma, 2005)
Abate, Alberto ; Bertocci, Carlo ; Ciroli, Eleonora ; demetz, aron ; Fabrizi, Stefania ; Forns Bada, Carlos ; Gálvez, Alberto ; Holland, Harry ; Kirby, John ; Marrone, Salvatore ; Mileto, Stefania ; Pedrazzi, Massimo ; Reggio, Mauro ; Russo, Salvo ; Salvo, Lily ; Scarpella, Livio ; Tirelli, Giuseppe ; Tonelli, Giorgio ; Valls, Dino ; Ventrone, Luciano ; Volpi, Angela ; Zucchi, Fernando
Italiaans
boek